2013
DOI: 10.1088/0004-6256/146/3/63
|View full text |Cite
|
Sign up to set email alerts
|

Secular Behavior of Exoplanets: Self-Consistency and Comparisons With the Planet-Planet Scattering Hypothesis

Abstract: If mutual gravitational scattering among exoplanets occurs, then it may produce unique orbital properties. For example, two-planet systems that lie near the boundary between circulation and libration of their periapses could result if planet-planet scattering ejected a former third planet quickly, leaving one planet on an eccentric orbit and the other on a circular orbit. We first improve upon previous work that examined the apsidal behavior of known multiplanet systems by doubling the sample size and includin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 62 publications
3
12
0
Order By: Relevance
“…Changing β to more extreme values would not change our main conclusion because, even if the number of collisions per ejection decreases, showed that the eccentricity of the surviving planet after the ejection would decrease with decreasing β (for reference Ford & Rasio 2008 find e 0.2 for β = 1/9). Likewise, the final inclinations after ejections are also limited as one decreases β (e.g., Timpe et al 2013). In conclusion, the excitation of eccentricities and inclinations is inefficient even if the mass ratio departs from unity.…”
Section: Planet Mass Ratio: βmentioning
confidence: 90%
“…Changing β to more extreme values would not change our main conclusion because, even if the number of collisions per ejection decreases, showed that the eccentricity of the surviving planet after the ejection would decrease with decreasing β (for reference Ford & Rasio 2008 find e 0.2 for β = 1/9). Likewise, the final inclinations after ejections are also limited as one decreases β (e.g., Timpe et al 2013). In conclusion, the excitation of eccentricities and inclinations is inefficient even if the mass ratio departs from unity.…”
Section: Planet Mass Ratio: βmentioning
confidence: 90%
“…Specifically we focus on the "Mixed2" distribution of Raymond et al (2008) in which the planets' masses follow a power-law distribution with exponent −1.1. This distribution has recently been shown to reproduce many observed dynamical properties of exoplanets (Timpe et al 2013). This suite of simulations consisted of 1000 systems, and we examined 49 that had period ratios with 10% of 2, of which 24 were identified as being in an e-resonance by Raymond et al (2008).…”
Section: Formation By Scatteringmentioning
confidence: 99%
“…The simulations we used were presented in several previous studies of planet-planet scattering and its consequences (Raymond et al 2008(Raymond et al , 2009(Raymond et al , 2010Timpe et al 2013). We focused on a particular set of simulations referred to as the mixed set in previous papers.…”
Section: Eccentricitiesmentioning
confidence: 99%
“…For multi-planet systems, additional constraints are imposed on eccentricity values due to the requirement that the system remain dynamically sta-ble. Dynamical interactions of multi-planet systems in the context of eccentricity and formation models have been investigated by numerous authors Jurić & Tremaine 2008;Malmberg & Davies 2008;Matsumura et al 2008;Raymond et al 2008Raymond et al , 2010Wang & Ford 2011;Timpe et al 2013). From the known multi-planet systems, there are four in particular which stand out with respect to the diversity of eccentricities present within the system.…”
Section: Introductionmentioning
confidence: 99%